2017
DOI: 10.5588/ijtld.17.0162
|View full text |Cite
|
Sign up to set email alerts
|

Does antiretroviral treatment increase the infectiousness of smear-positive pulmonary tuberculosis?

Abstract: BACKGROUND: Understanding of the effects of human immunodeficiency virus (HIV) infection and antiretroviral treatment (ART) on Mycobacterium tuberculosis transmission dynamics remains limited. We undertook a cross-sectional study among household contacts of smear-positive pulmonary tuberculosis (TB) cases to assess the effect of established ART on the infectiousness of TB. METHOD: Prevalence of tuberculin skin test (TST) positivity was compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This increase in the number of infected contacts of drug-resistant index cases could be due to prolonged duration of infectiousness in drug-resistant tuberculosis as a result of diagnostic delays. 26 Immunosuppressed HIV-positive index cases with drug-susceptible tuberculosis are less likely to transmit to household contacts than HIV-negative cases, 27–31 probably due to aforementioned differences in cavitation and bacillary load. 27,2931 Contact investigation in rural South Africa 32 has also shown the force of infection in an HIV-endemic setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in the number of infected contacts of drug-resistant index cases could be due to prolonged duration of infectiousness in drug-resistant tuberculosis as a result of diagnostic delays. 26 Immunosuppressed HIV-positive index cases with drug-susceptible tuberculosis are less likely to transmit to household contacts than HIV-negative cases, 27–31 probably due to aforementioned differences in cavitation and bacillary load. 27,2931 Contact investigation in rural South Africa 32 has also shown the force of infection in an HIV-endemic setting.…”
Section: Introductionmentioning
confidence: 99%
“…26 Immunosuppressed HIV-positive index cases with drug-susceptible tuberculosis are less likely to transmit to household contacts than HIV-negative cases, 27–31 probably due to aforementioned differences in cavitation and bacillary load. 27,2931 Contact investigation in rural South Africa 32 has also shown the force of infection in an HIV-endemic setting. It was found that, of 793 contacts of multidrug-resistant tuberculosis index cases, 14 (1.8%) were diagnosed with multidrug-resistant tuberculosis (incidence 1765 of 100 000) and 19 (2.0%) of 973 extensively drug-resistant tuberculosis contacts had extensively drug-resistant tuberculosis (incidence 1952 of 100 000) within a median of 70 days (IQR 57–89) of index case diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[31] There is uncertainty over the role of HIV in the infectiousness of pulmonary tuberculosis, particularly with immune reconstitution due to ART. [32] This is partly because of the lack of a robust test for diagnosis of recent TB infection in settings where community force of infection is high, and data suggesting that HIV infection may lead to a shorter duration of symptomatic pulmonary disease and with less cavitation and lower bacillary load in people living with HIV. [33] In a high-TB burden community, TST induration in a household contact may represent infection as a consequence of household exposure from an index case, infection from other community contacts, or both.…”
Section: Plos Onementioning
confidence: 99%
“…Of the 40 publications on TB patient support, 36 included treatment supervision options [ 9 , 28 , 39 48 , 30 , 49 , 50 , 52 – 54 , 56 – 60 , 31 , 62 , 64 67 , 32 , 33 , 35 – 38 ] (19 as the sole patient support intervention [ 9 , 29 , 39 , 41 , 42 , 45 , 48 , 50 , 58 , 64 , 30 – 33 , 35 – 38 ]), 12 included SE support [ 34 , 43 , 61 , 62 , 46 , 47 , 52 , 53 , 56 , 57 , 59 , 60 ] (1 as the sole intervention [ 61 ]), 11 included PE support [ 34 , 40 , 62 , 51 , 53 – 57 , 59 , ...…”
Section: Resultsmentioning
confidence: 99%